Die kompromie in die etiek: méér as net ’n besluitnemingsfiguur in die etiek - Lategan, LOK (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
Although the concept of a compromise is known in ethics, very little attention has been paid to the meaning of this concept in Reformed Ethics. In analysing this concept, it is pointed out that a compromise has to do with the choice between two conflicting norms in a borderline situation. In a borderline situation these norms are in conflict with each other and a conflict of interest is created. It then necessitates a choice between one of the norms in a borderline situation. To this choice is then referred to as a choice between the lesser of two evils. This is where the compromise comes into play. The author also points out that a compromise and consensus are not the same. Against the background of a theology of the Kingdom of God, the compromise is an act of obedience.